DAMPAK CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PERBANKAN SYARIAH INDONESIA TAHUN 2007-2011 - Virda Rakhma Septiputri; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
This study aims to examine the impact of corporate governance mechanisms: size of theboard of directors, board of commissioners size, proportion of independent commissioners, size ofthe Sharia Supervisory Board, and the reputation of the Public Accounting Firm on profitability asmeasured by Return on Equity (ROE).This study is an empirical research with the pooling technique in data collection. Dataobtained from the financial statements and the annual report Sharia Commercial Bank the periodof 2007 to 2011 with total 30 data. Multiple regression analysis was conducted by using SPSSversion 16 for Windows.The test results showed that size of the board of directors has positive and significanteffect to profitability.